The change of the electrophysiological parameters using human intestinal tissues from ulcerative colitis and Crohn's disease - Daisuke Nakai; Masateru Miyake (Elsevier, 2022)
The purpose of this study was to investigate how disease state of the UC and CD patients affect tissue function determined from electrophysiology viewpoint the electrophysiological parameters on normal, ulcerative colitis (UC) and Crohn's disease (CD) patients. Potential differences (PD), short circuit current (Isc) and resistance (R) as electrophysiological parameters were determined using human large intestinal tissues.The measure of autoptical abnormality was quantified on an arbitrary scale of 0-2. A severe effect of ulcer and thickened mucosa by fibrosis was scored as Grade 2. The larger number of autopsy grade on both UC and CD tissues, the lower values of PD and R than those of normal tissues were observed, although Isc values were not statistically changed irrespective of autopsy grade. This electrophysiological observation of reduced PD indicated functional impairment of active ion transport via ion pumps. Additionally, the R values of CD tissues on each autopsy grade tended to be lower than those of UC tissues. These results suggest that the effect of inflammatory bowel disease on barrier function is different between UC and CD tissues. Therefore, the fibrosis on CD patients might affect the electrophysiological parameters than that of UC patients.